2009
DOI: 10.1038/ncb1993
|View full text |Cite
|
Sign up to set email alerts
|

YAP-dependent induction of amphiregulin identifies a non-cell-autonomous component of the Hippo pathway

Abstract: The Hippo signaling pathway regulates cellular proliferation and survival, thus exerting profound effects on normal cell fate and tumorigenesis1-3. The pivotal effector of this pathway is YAP, a transcriptional co-activator amplified in mouse and human cancers, where it promotes epithelial to mesenchymal transition (EMT) and malignant transformation4-10. To date, studies of YAP target genes have focused on cell-autonomous mediators; here we show that YAP-expressing MCF10A breast epithelial cells enhance the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
313
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 372 publications
(341 citation statements)
references
References 31 publications
18
313
2
1
Order By: Relevance
“…7D). The expression of the YAP target gene for amphiregulin (Areg) (41,42) was also significantly increased in crypts of the mutant mice (Fig. 7E).…”
Section: Generation Of Iec-specific Csk Cko Micementioning
confidence: 92%
“…7D). The expression of the YAP target gene for amphiregulin (Areg) (41,42) was also significantly increased in crypts of the mutant mice (Fig. 7E).…”
Section: Generation Of Iec-specific Csk Cko Micementioning
confidence: 92%
“…Furthermore, Yki-Sd was shown to transcriptionally induce dMyc, a potent promoter of ribosome biogenesis and cell growth (Neto-Silva et al, 2010;Ziosi et al, 2010), which may mediate the cell competition phenomenon observed in tissues with imbalance of Hippo pathway activity. In addition, Yki induces E2F1 (Goulev et al, 2008), which may be involved in cell-autonomous regulation of cell proliferation; the EGFR ligands Vein, Keren, and Spitz (Zhang et al, 2009b;Ren et al, 2010); the Jak/Stat pathway ligands Unpaired1/2/3 (Upd1/2/3) (Karpowicz et al, 2010;Ren et al, 2010;Shaw et al, 2010;Staley and Irvine, 2010), which could mediate non-cell-autonomous function of the Hippo pathway; and the Hippo pathway genes Ex, Kibra, Crb, and Fj (Cho et al, 2006;Hamaratoglu et al, 2006;Genevet et al, 2009;Genevet et al, 2010), which may constitute a signal feedback loop.…”
Section: The Drosophila Hippo Pathwaymentioning
confidence: 99%
“…CTGF alone, however, does not account for all YAP phenotypes. YAP and TAZ also induce the expression of AREG (Zhang et al, 2009b) and FGF1 (Hao et al, 2008), which may also mediate non-cell-autonomous function of the Hippo pathway. However, the mechanisms underlying the induction of these genes, including the responsible transcription factors, are mostly unclear.…”
Section: The Mammalian Hippo Pathwaymentioning
confidence: 99%
“…However, this has changed, as a recent study identified the epidermal growth factor receptor (EGFR) ligand Amphiregulin as a transcriptional target of the Hippo pathway in mammals 83 , and showed that activation of YAP leads to proliferation of neighboring cells in an EGRF dependent manner. This study also demonstrated that Yorkie shows genetic interactions with the EGFR in flies, suggesting that alterations in Hippo pathway activity will have nonautonomous effects in both normal development and in cancers.…”
Section: Bountiful Crosstalk In the Hippo Pathwaymentioning
confidence: 99%